Effectiveness of Intensive Motor Learning Approaches for Stroke: A Systematic Review of Randomized Controlled Trials. - Jamkar, Mayuresh; Giri, Sanjana; Jeyakumar, S.; Vignesh, Thillai (Indian Journal of Physiotherapy & Occupational Therapy)
Background: Stroke is a major contributor to long-term disability worldwide, presenting significant obstacles to motor function, coordination, and independence. Rehabilitation approaches to those deficits include intensive motor learning strategies aimed at promoting neuroplasticity that will lead to functional recovery. This systematic review examined the effectiveness of different motor learning-based interventions in stroke rehabilitation, including, but not limited to, constraint-induced movement therapy (CIMT), task-specific training (TST), robotics-assisted therapy, virtual reality interventions, and Hand-Arm Bimanual Intensive Therapy Including Lower Extremities (HABIT-ILE). Methods: A systematic search on PubMed, the Cochrane Library, and Google Scholar identified studies published in the last decade that examined intensive motor learning interventions with respect to stroke rehabilitation. The search yielded 4871 studies, leading to the final selection of ten studies that met strong inclusion criteria. To promote methodological rigor, the PRISMA framework was used. Primary outcome measures were motor function improvements, neuroplasticity changes, and functional independence levels. Results: The results show HABIT-ILE, TST and virtual reality-based interventions displayed significant and long-lasting improvements in motor function, coordination, and independence. CIMT needs more research and while it has promise, we do not know how it will compare long-term and the evidence is mixed regarding its effectiveness in reducing disability levels. Robotics-assisted therapy improves motor learning and strength, but there are still challenges in applying these improvements to activities of daily living (ADLs). Conclusion: It is essential to incorporate various intensive motor learning strategies instead of depending only on traditional therapy to maximize stroke rehabilitation. Interventions such as HABIT-ILE and task-specific training show great promise, and new technologies like virtual reality and robotics provide extra advantages. Nonetheless, more research is necessary to improve intervention protocols, create standardized outcome measures, and design personalized rehabilitation strategies to enhance motor recovery for stroke survivors. Categories: Physical Medicine & Rehabilitation, Therapeutics, Motor Learning, Neurorehabilitation